2020
DOI: 10.1177/1049909120979982
|View full text |Cite
|
Sign up to set email alerts
|

The Premise and Development of CHECK IN—Check-In for Exchange of Clinical and Key Information to Enhance Palliative Care Discussions for Patients With Limited English Proficiency

Abstract: Communication regarding serious illness is challenging in most circumstances. Patients with Limited English Proficiency (LEP) have unique language and cultural needs that often require collaboration with a trained medical interpreter, especially when the clinical encounter involves serious illness decision making or elucidation of patient goals, preferences, and values. Although there is mounting evidence to support interpreter/clinician huddles before a serious illness communication encounter, no current init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…There is limited comparative literature exists evaluating factors associated with favorable attitudes regarding the role of medical interpreters or best communication practices when utilizing medical interpreters during EOL and GOC conversations. 10,15,20,33,34 Other studies evaluating healthcare providers’ utilization practices and attitudes toward medical interpreters in EOL care, have found that medical interpreters are underused and healthcare providers lack familiarity with their interpreting roles and lack skills needed to work effectively with medical interpreters in language discordant interactions. 23,28,34…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited comparative literature exists evaluating factors associated with favorable attitudes regarding the role of medical interpreters or best communication practices when utilizing medical interpreters during EOL and GOC conversations. 10,15,20,33,34 Other studies evaluating healthcare providers’ utilization practices and attitudes toward medical interpreters in EOL care, have found that medical interpreters are underused and healthcare providers lack familiarity with their interpreting roles and lack skills needed to work effectively with medical interpreters in language discordant interactions. 23,28,34…”
Section: Discussionmentioning
confidence: 99%
“…There is growing literature that in-person medical interpreters enhance the quality of communication during EOL and GOC conversations with LEP patients. 15,27,29,33-35,38-40 Despite the vast evidence of the benefits of using in-person medical interpreters 9,11-15,27,33,38,39,41 including being able to provide more personable communication and identifying non-verbal cues that are important in communication, there are some organizational limitations that affect their utilization. Access to in-person medical interpreters varies greatly by institution and is often not available due to time constraints and expense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the COVID-19 pandemic strategies beyond language interpretation to support patients with LEP have included specific clinic days with language-congruent clinicians [46], huddles between clinicians and interpreters [47], continuing education sessions on caring for patients with LEP [48], electronic apps for health promotion and communication providers [49], and chronic disease education via group video visits by community health workers [50]. Most interventions described in the literature occur in non-hospitalized patients, such those seen in outpatient clinics or through community outreach [46,49,51].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst an assumption was made that the preferred language of deceased patients and Next-of-Kin were the same, these data indicate underuse of professional interpreters; a surprising finding given language is one of the most significant barriers to high-quality end-of-life care 15 and professional interpreters are fundamental to ensuring effective, person-centred and culturally-sensitive communication. 16 Formal family meetings are essential to optimal care planning, particularly when death is anticipated. 17 These findings suggest a missed opportunity to also use formal family meetings to gather information that can be used to inform practices to support families and raise the question of why anticipated death did not trigger an assessment of family support needs, and routine referral/involvement of social work and pastoral care.…”
Section: Discussionmentioning
confidence: 99%